Determination of Acid Dissociation Constant of Pravastatin under Degraded Conditions by Capillary Zone Electrophoresis - TAKAYANAGI, Toshio; AMIYA, Mika; SHIMAKAMI, Natsumi; YABUTANI, Tomoki (Analytical Sciences, 2015)
The acid dissociation constant of pravastatin was determined under degraded conditions. Pravastatin was degraded in an acidic solution (pH = 2.0) for 5 h, and the degradation solution was subjected to the measurement of the effective electrophoretic mobility by capillary zone electrophoresis. Although the amount of pravastatin decreased by the acid degradation, its acid dissociation constant was successfully determined with the residual pravastatin through its effective electrophoretic mobility. The determined acid dissociation constant value agreed well with the one obtained with freshly prepared solution and with some reported values.